Multi-tier cropping system: An alternative practice for small land holdings in tribal area - Bisen, Abhay; Jain, Vinamarta; Singh, S. R. K.; Narayan, Hari (Indian Farming, 2025)
The multi-tier cropping system, also known as multi-layer farming, is an innovative approach designed to maximize agricultural productivity for small landholders, especially in tribal areas. By cultivating multiple crop species at different heights on the same plot, this system utilizes vertical and horizontal dimensions to create a multi-layered ecosystem that enhances resource efficiency and biodiversity. Implemented under the Farmer FIRST Programme by SKS College of Agriculture and Research Station, this model was demonstrated in select villages of Chhattisgarh to support sustainable agriculture for tribal farmers. The method allows for higher yields, reduced pest infestation, increased biodiversity, and better economic returns per unit area. Multi-layer farming has proven effective in providing year-round income, fostering environmental sustainability, and offering a viable solution for small and marginal farmers in resource-constrained areas.